Evaluation of the effects of two different bone resorption inhibitors on osteoclast numbers and activity: An animal study - Narges Naghsh; Sayed Mohammad Razavi; Mohsen Minaiyan; Mohammad Shahabooei; Reza Birang; Parichehr Behfarnia; Samira Hajisadeghi (Wolters Kluwer Medknow Publications, 2016)
Background: The aim of this study was to evaluate the effects of bone resorption inhibitors, doxycycline (DOX) and erythromycin (EM), on osseous wound healing in rat alveolar socket. Materials and Methods: In this randomized controlled trial, 45 8-10-week-old male Wistar rats had their maxillary right molar extracted. They were divided into three groups of 15. In Group 1 normal saline, Group 2 DOX, and Group 3 EM were administered at the doses of 5 ml/kg/day, 5 mg/kg/day, and 2 mg/kg/day, respectively, for 7 consecutive days. The rats were sacrificed 7, 14, and 21 days after surgery. Real-time polymerase chain reaction was employed to evaluate the mRNA expression of receptor activator of nuclear factor κB ligand (RANKL) and osteoprotegerin (OPG) and immunohistochemical staining for tartrate-resistant acid phosphatase (TRAP) to determine osteoclasts. The data were analyzed by one-way analysis of variance followed by Tukey's post hoc test using SPSS version 20. Significant level was set at 0.05. Results: The results showed that when drug-treated groups compared to control groups, RANKL gene expression significantly decreased, TRAP+ cells decreased on day 7. The RANKL/OPG ratios in the first two weeks in the test groups were significantly lower than the control group. There was no significant difference in the studied indices between DOX and EM groups. Conclusion: Following administration of DOX and EM, the number of osteoclasts and RANKL/OPG ratio decreased suggesting their anti-osteoclastogenesis activity. These two drugs have no advantage over each other in increasing the bone formation.